A study on the training needs of Sabah Sports Board's employees / Colette Anthung Dainal - Anthung Dainal, Colette (2010)
This study analyzes the training needs assessment of Sports Complexes under the jurisdiction of Sabah Sports Board. It aims at identifying the types of training programs, methods of training and the barriers that prevent the effectiveness implementation of training program. The Sports Complexes which were the unit of analysis in this study were the Kota Kinabalu Sports Complex, Penampang Sports Complex, Sandakan Sports Complex, Tawau Sports Complex, Keningau Sports Complex, Ranau Sports Complex and Tambunan Sports Complex. Identification of types and methods of training program are important for Sabah Sports Board to ensure that every employee of Sports Complexes are knowledgeable, skillful and full of abilities that will contribute to increased revenue, customer satisfaction and quality sports facilities services.